EMPLOYING CHAOS THEORY IN SELECT CARTOONS OF NODDY: UNVEILING THE UNPREDICTABLE - Mathew, Leena Liz; D. R., Fancy; Joseph, Solomon Asha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Chaos Theory looks at the amazing unpredictability of nature. It has captured the beauty of the unpredictable and exhibited it in the most awesome patterns. It proposes that all seemingly natural systems are in fact controlled by complex and mysterious forces known as “strange attractors”, forces which are both random and determined. It is a peculiar paradox – it is the prediction of the behaviour of “inherently unpredictable” systems. The most important feature of chaotic systems is the conscious dependence on initial conditions. Television shows based on Noddy; an English character created by Enid Blyton have been telecasted on British television from 1955 to 2020. The paper discusses how the principles of Chaos theory can be applied in the cartoons ‘Noddy and the Dancing Spell’, ‘Noddy’s Car Trouble’ and ‘Noddy Needs Some Medicine’. Chaotic systems have a predictable nature for some time and then seemingly become arbitrary. Strange attractors are symbolic of a chaotic system. Small things can be counted as catalysts, and they act on initial conditions. The cartoons selected exhibits how certain situations are sensitive and how a slight variation in the primary phase can create quite a difference in where they end up. The structures around us are chaotic and they are prone to abrupt modifications. The chaotic systems are always there in our real-life situations. These cartoons portray examples of such real-life situations. Even the minute things that go unnoticed can cause very large problems. The chaotic systems are enough to make highly complex problems, and such complex happenings can be overwhelming